Identify Mens Rea in Language use from a Criminal Law Perspective - Kurniawati, Rizki; ., Armansyah; Marbun, Rocky (KnE Social Sciences, 2024)
This article explains and identifies the existence of mens rea in the dissemination of news packaged into content through various social media platforms, implicitly containing hate speeches, so that it can be viewed as an electronic-based criminal offense uploaded either verbally or non-verbally. An ability to communicate within the scope of society in the use of language is not owned by everyone, especially in the era of social media where there are those who use language in an inappropriate way. For example, it is used for swearing, defamation, making fake news or hoaxes, threats, persecution speech, to hate speeches that can harm the interlocutor. This study aims to determine the existence of mens rea in the use of language about hate speech committed by individuals through social media platforms. Their point of view will be studied through the perspectives of criminal law. The study’s objective was to examine the use of language in individual uploads through several social media platforms that contain hate speech and ‘SARA in the context of criminal law. In sampling, the author uses descriptive qualitative research methods and legal research methods based on the available data. Keywords: mens rea, language, blasphemy, criminal law